Discovering your selling points: Personalized social influential tags exploration - LI, Yuchen (Institutional Knowledge at Singapore Management University, 2017)
Social influence has attracted significant attention owing to the prevalence of social networks (SNs). In this paper, we study a new social influence problem, called personalized social influential tags exploration (PITEX), to help any user in the SN explore how she influences the network. Given a target user, it finds a size-k tag set that maximizes this user’s social influence. We prove the problem is NP-hard to be approximated within any constant ratio. To solve it, we introduce a sampling-based framework, which has an approximation ratio of 1−ǫ 1+ǫ with high probabilistic guarantee. To speedup the computation, we devise more efficient sampling techniques and propose best-effort exploration to quickly prune tag sets with small influence. To further enable instant exploration, we devise a novel index structure and develop effective pruning and materialization techniques. Experimental results on real large-scale datasets validate our theoretical findings and show high performances of our proposed methods.